EMPIRE AND POPULAR CULTURE ([S.l.])
1 online resource
Keywords: From 1830, the British Empire began to permeate the domestic culture of Empire nations in many ways. This, the fourth volume of Empire and Popular Culture, explores the representation of the Empire in popular media such as newspapers, contemporary magazines and journals and in literature such as novels, works of non-fiction, in poems and ballads.